Combined transfer by several perforator skin flaps to cover an extensive and multiplanar wound on the foot and ankle. Issue 10 (October 2022) - Ou, Qifeng; Wu, Panfeng; Pan, Ding; Tang, Ju-yu
Abstract: Background: This study aimed to assess the feasibility and effectiveness of using combined transfer by two or three large skin flaps to cover a single extensive and multiplanar wound on the foot and ankle to achieve full coverage of the wound and primary donor-site closure. Patients and methods: Seventeen patients with extensive wounds around their foot and ankle were treated. The flap could either be anterolateral femoral perforator (ALTP) flap, deep inferior epigastric artery perforator (DIEP) flap, or thoracodorsal artery perforator (TDAP) flap. According to the dimensions and shape of the wound and the availability of donor sites, we classified the reconstruction into three different types. Based on the type, the soft-tissue defect was divided into two or three parts to guide the corresponding perforator skin flaps to be harvested within the maximum width and length of the donor sites. Results: All 17 patients were successfully reconstructed, with a total of 35 flaps in 37 paddles. Vascular compromise occurred in one patient and was saved by venous thrombectomy. In total, four flaps experienced a partial loss and were treated either conservatively or by a skin graft. No ulceration due to abrasion occurred on any flap during the entire follow-up. All donor sites were directly closed and healed uneventfully, except for one needing coverage by a skin graft and another experiencing dehiscence and scar widening. Conclusion: Combined transfer by several skin perforator flaps is a flexible reconstructive option for resurfacing extensive and multiplanar wounds on the foot and ankle. The benefit lies in a well-reconstructed contour, an anti-frictional property, a permission of a normal shoe wearing in the reconstructed foot, and meanwhile a primary closure on donor site.